"But there is a God": Teaching Nat Turner in early childhood education. (December 2022) - Johnson, Marcus W
This study set out to gain a deeper understanding of how early childhood students, specifically Black boys in first and second grade, would respond to the teaching of historical figures and events traditionally omitted from classrooms. Contrary to general assumptions, these students were able to astutely contribute to classroom lessons, discussions, and interviews about Nat Turner, an enslaved Black American, who led a rebellion in 1831. Employing notions of Black intellectual thought and curricular and pedagogical resuscitation as theoretical frameworks, in addition to critical hermeneutic phenomenology as its methodology, this study highlights the voices of young Black boys often missing in early childhood discourse. Findings indicate that the students expressed a favorable assessment of Nat Turner and his comrades. The statement, "But there is a God, " ultimately confronts the unavailability and restricted options for Black humanity in a racist society, but also an awareness testifying to a self-ordained defense of the Black body. This study gives added perspective to the understanding of the early learning process, cultural meaning-making, and connection to a Black educational legacy spanning generations.